Human bioclimate analysis for the Paris Olympic Games - Matzarakis, A.; Graw, K. (Atmosphere, 2022)
Weather and climate conditions can be important and a decision factor for travel plans or outdoor and sport events. It is important to quantify thermal comfort and other related climate factors for different applications and destinations and make the results easily accessible to visitors and sport attendees. This analysis has provided and quantified thermal comfort, heat stress and other climate-related factors. A relevant approach is the visualization of climate thresholds in a Climate-Tourism/Transfer-Information Scheme (CTIS) for the prevailing local climate conditions. The methodology provided here is a possible gold standard of good human biometeorological practices for tourism, recreation and sports, and can be applied for all major events. The information provided on the local climate can be extracted by non-experts such as tourists intending to attend sports events.